2017
DOI: 10.1088/1361-665x/aa7042
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric power generation using friction-induced vibration

Abstract: In order to examine the feasibility of power generation by using friction-induced vibration with a piezoelectric element, we performed experiments and numerical analysis. In the experiments, the generated power in the piezoelectric element and the displacement of an oscillator were measured by a newly developed apparatus that embodied a single-degree-of-freedom (1-DOF) system with friction. In the numerical analysis, an analytical model of a 1-DOF system with friction and piezoelectric element was proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…A friction system with two DOFs is employed to study the PEH via FIV; this system is extended from the work of Tadokoro et al [53]. In their work, a ball sample rubs against a sliding flat sample and stick-slip motion occurs; then a piezoelectric film is attached with the fixture of the test setup and successfully transfers the FIV energy to electric energy.…”
Section: Theoretical Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…A friction system with two DOFs is employed to study the PEH via FIV; this system is extended from the work of Tadokoro et al [53]. In their work, a ball sample rubs against a sliding flat sample and stick-slip motion occurs; then a piezoelectric film is attached with the fixture of the test setup and successfully transfers the FIV energy to electric energy.…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…e parameters set in this analysis are from the work performed by Tadokoro et al [53], which are listed in Table 1. Figure 3 depicts the variation of real and imaginary parts of the eigenvalues with the increase of friction coefficients.…”
Section: Eigenvalue Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a new and alternative approach was proposed by various studies to solve this problem, which involves harvesting the vibration energy of friction-induced vibration (FIV). FIV does not rely on the external excitation of the environment vibration source [21][22][23]. Considering that FIV may cause the generation of unwanted noise (known as frictioninduced vibration and noise (FIVN)), which is often detrimental to people's health and affects operations of machines and functions of structures, a large number of studies on FIV have found potential approaches to reduce it [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Tsujiura et al [36] built a self-excited piezoelectric film twin-chip airflow energy harvester and found that a thinner cantilever reduced the maximum output voltage. Tadokoro et al [37] established an analytical model of a 1-degree-offreedom system with friction and piezoelectric elements, which can be applied to the optimization design of a friction-excited piezoelectric generator oscillator. Several investigations have also verified the feasibility of PEH via stick-slip friction motion using different test setups [38][39][40].…”
Section: Introductionmentioning
confidence: 99%